2017
DOI: 10.18632/oncoscience.383
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix composition modulates angiosarcoma cell attachment and proliferation

Abstract: Angiosarcoma is a rare and generally fatal tumor composed of aberrant cells of endothelial origin. Because of its infrequency in humans, very little is known about the growth requirements of this vascular sarcoma. Unlike the rapidly proliferating solid tumors from which they are isolated from, many of the established angiosarcoma cell lines exhibit less than robust growth in culture and often fail to form tumors in xenograft models. In order to better understand angiosarcoma in vitro growth conditions, we focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…GSEA [32,33] indicated that the mouse angiosarcoma upregulated genes were also significantly enriched in human angiosarcomas (Figure 1C). Finally, gene ontology analysis of the 123 overlapping genes revealed terms related to cell cycle, extracellular matrix, and blood vessel development (Figure 1D and supplementary material, Table S4) consistent with recent findings in human and canine tumors emphasizing the role of extracellular matrix [12,38]. Furthermore, pathway analysis of genes enriched in the AKC cKO and AD cKO tumors revealed KEGG pathways such as RAP1 signaling, pathways in cancer, axon guidance, MAPK signaling, and focal adhesion (see supplementary material, Table S4).…”
Section: Disparate Angiosarcoma Mouse Models Converge On Ras-mek-erk ...supporting
confidence: 86%
“…GSEA [32,33] indicated that the mouse angiosarcoma upregulated genes were also significantly enriched in human angiosarcomas (Figure 1C). Finally, gene ontology analysis of the 123 overlapping genes revealed terms related to cell cycle, extracellular matrix, and blood vessel development (Figure 1D and supplementary material, Table S4) consistent with recent findings in human and canine tumors emphasizing the role of extracellular matrix [12,38]. Furthermore, pathway analysis of genes enriched in the AKC cKO and AD cKO tumors revealed KEGG pathways such as RAP1 signaling, pathways in cancer, axon guidance, MAPK signaling, and focal adhesion (see supplementary material, Table S4).…”
Section: Disparate Angiosarcoma Mouse Models Converge On Ras-mek-erk ...supporting
confidence: 86%
“…It has been reported that IL-6 and CXCL8 levels are related to the degree of liver fibrosis and can promote the process of liver fibrosis by inducing HSCs activation and regulating apoptosis [ 39 43 ]. It has also been shown that AKT regulates ECM degradation and that HSC activation aggravates liver fibrosis [ 44 ]. MAPK can induce liver inflammation and fibrosis, increase the extracellular matrix and affect the hypoxia inducible factor 1 subunit alpha (HIF-1 α ) signaling pathway to stimulate proliferation and activation of HSCs [ 45 – 49 ].…”
Section: Discussionmentioning
confidence: 99%